Effect of Curcumin on VEGF Expression and Cell Migration in Human Pterygium Fibroblast - Zhafira, Dinda; Primitasari, Yulia; Lutfi, Delfitri; Komaratih, Evelyn; Indriaswati, Luki; Ardianto, Chrismawan (South Eastern European Journal of Public Health, 2024)
This review investigates the effects of curcumin, a polyphenol derived from turmeric, on vascular endothelial growth factor (VEGF) expression and cell migration in human pterygium fibroblasts (HPFs). Pterygium, a degenerative and inflammatory condition of the ocular surface, is characterized by excessive fibrovascular growth often linked to UV radiation exposure. The study highlights curcumin's anti-inflammatory, anti-angiogenic, and antioxidant properties, demonstrating its ability to significantly reduce VEGF expression and inhibit cell migration in HPFs. The findings suggest that curcumin may serve as a novel adjuvant therapy to decrease pterygium recurrence by targeting key pathways involved in its pathogenesis, thus offering a promising alternative to traditional surgical interventions.